A new perspective on Alzheimer’s disease: m6A modification - Xia, Lei; Zhang, Fan; Li, Yulu; Mo, Yuemi; Zhang, Lingqiu; Li, Qianhua; Luo, Minghuang; Hou, Xiaotao; Du, Zhengcai; Deng, Jiagang; Hao, Erwei (Frontiers in Genetics, 2023)
As a neurodegenerative disease, Alzheimer's disease (AD) is characterized by synaptic loss, extracellular plaques of amyloid A, hyperphosphorylation of tau, and neuroinflammation. Various biological processes are affected by epigenetic modifications, which regulate the metabolism of mRNA in cells and regulate the expression of genes. In response to changes in m6A modification levels, the nervous system becomes dysfunctional and plays a significant role in the development of Alzheimer's disease. As a result of recent research, this paper reviews advances in the understanding of the regulatory mechanisms of m6A modification in the occurrence and development of AD. In addition, the article discusses recent research techniques related to animal models of m6A and AD. Furthermore, it discusses the possibility of studying the pathogenesis of AD at the level of the epitranscriptome, identifying early diagnostic markers, and screening for effective treatment options.